Centered triangular difference mean graphs - Jeyanthi P.; Selvi M.; Ramya D. (Utilitas Mathematica, 2019)
A graph G = (V, E) with p vertices and q edges is said to have centered triangular difference mean labeling if there is an injective mapping f: V(G)→ Z+such that for each edge e = uv, f ∗(e) = [1f(u)-(v)/2 and the resulting edge labels are the first q centered triangular numbers. A graph that admits a centered triangular difference mean labeling is called a centered triangular difference mean graph. In this paper, we prove that the path Pn, K1,n, Cno˙ K1, Bm,n, Cn(n > 4), coconut tree, caterpillar S(n1,n2, n3,...,nm), Cn@Pm(n > 4) and Sm,nare centered triangular difference mean graphs. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.